The uptake and utility of genetic testing and genetic counseling for hypertrophic cardiomyopathy—A systematic review and meta‐analysis. Issue 6 (7th July 2022) - Cirino, Allison L.; Harris, Stephanie L.; Murad, Andrea M.; Hansen, Brittany; Malinowski, Jennifer; Natoli, Jaime L.; Kelly, Melissa A.; Christian, Susan
Abstract: Genetic testing and genetic counseling are routinely indicated for patients with hypertrophic cardiomyopathy (HCM); however, the uptake and utility of these services is not entirely understood. This systematic review and meta‐analysis summarizes the uptake and utility of genetic counseling and genetic testing for patients with HCM and their at‐risk family members, as well as the impact of genetic counseling/testing on patient‐reported outcomes (PROs). A systematic search was performed through March 12, 2021. Meta‐analyses were performed whenever possible; other findings were qualitatively summarized. Forty‐eight studies met inclusion criteria (47 observational, 1 randomized). Uptake of genetic testing in probands was 57% (95% confidence interval [CI]: 40, 73). Uptake of cascade screening for at‐risk relatives were as follows: 61% for cascade genetic testing (95% CI: 45, 75), 58% for cardiac screening (e.g. echocardiography) (95% CI: 40, 73), and 69% for either/both approaches (95% CI: 43, 87). In addition, relatives of probands with a positive genetic test result were significantly more likely to undergo cascade screening compared to relatives of probands with a negative result (odds ratio = 3.17, 95% CI: 2.12, 4.76). Overall, uptake of genetic counseling in both probands and relatives ranged from 37% to 84%. Multiple studies found little difference in PROs between individuals receiving positive versus negative genetic test results; however, other studies found that individuals with positive genetic test results experienced worse psychological outcomes. Genetic testing may also inform life choices, particularly decisions related to reproduction and insurance. Genetic counseling was associated with high satisfaction, increased perceived personal control and empowerment, and decreased anxiety. Approximately half to three‐quarters of patients with HCM and their relatives undergo genetic testing or cascade screening. PROs after genetic testing varied and genetic counseling was associated with high satisfaction and improved PROs.